Mechanisms to support and accompany small and medium enterprises to activate the entrepreneurial spirit in Algeria - Mansour, Malika Lakhdar (Journal of Economic, Administrative and Legal Sciences, 2021)
The objective of this paper is to understand the role of entrepreneurship in activating the creation of small and medium enterprises among university students after the graduate academic was looking for a job, he became the one who creates and offers jobs, this is achievable by integrating and linking the entrepreneurial culture with the house of entrepreneurship with higher education programs through which it can acquire various professional, technical, managerial and personal skills and develop the spirit of 'company that cultivates creativity, initiative, risk and a culture of independent work that can be developed through aid and support.
Keywords: entrepreneurship; small and medium enterprises; support structures; initiative; work culture